Flow diverter treatment for saccular unruptured intracranial aneurysms: a systematic review focussing on study quality and initial outcomes - Wenz, Fabian; Wiedemann, Tamara; Rinkel, Gabriel J. E.; Etminan, Nima (European stroke journal, 2026)
Flow-diverting (FD) stents are increasingly used to treat small, unruptured intracranial aneurysms (UIA), but high-quality, unbiased data on initial complications and clinical outcomes were limited in previous literature reviews. We updated the literature review to assess quality, potential bias, complications and short-term outcomes in studies on FD-stents for UIAs.We systematically searched PubMed, Embase and Cochrane Library until January 9, 2025 for studies on FD-stents for UIAs. We assessed methodological quality using the methodological index for non-randomised studies (poor: 0-9, moderate: 10-13, good: 14-16), and financial conflicts of interest. The primary outcome was neurological outcome according to a validated outcome scale at 1-3 months after treatment. Secondary outcomes were clinical worsening and complications.We included 13 studies with 743 patients and 806 UIAs, of which 88.4% (95% CI: 85.7%-91.2%) were <10 mm. All studies were uncontrolled. The methodological quality was poor in six and moderate in seven studies. Financial conflicts of interest were reported in six studies. At 1-3 months after treatment, the proportion of patients were for mRS ⩾1 13.3% (95% CI: 10.0%-16.6%), mRS ⩾2 5.3% (95% CI: 3.2%-7.5%), mRS ⩾3 2.4% (95% CI: 0.1%-3.9%) and neurological worsening 3.1% (95% CI: 1.5%-4.6%). Complications within 3 months occurred in 12.7% (95% CI: 10.3%-15.0%).The literature on FD-stents is methodologically weak and potentially biased by financial interests but still shows relevant proportions of complications and post-treatment morbidity. Currently, there are no good data supporting the use of FD-stents for UIAs where standard treatment options are available. Randomised-controlled trials are needed to compare safety, efficacy and durability between FD-stents and coiling or clipping.
Gesehen am 24.02.2026